Marketing Mix Factors that Influence the Interest of Tourist Visits to Tourism Objects in Minahasa Tenggara Regency During the Covid-19 Pandemic - Mawu, Kendra Susan; A, Willem JF; Wulur, Magdalena (International Journal on Economics, Finance and Sustainable Development, 2021)
Tourism is an important source of income for a country. With the existence of tourism, a country or more specifically the Regional Government where the tourist attraction is located can earn income from the income of each tourist attraction. The purpose of this study was to determine whether the factors of the Marketing Mix (Product, Price, Place, Promotion) had a simultaneous or partial effect on Tourist Visiting Interests to tourist objects in Southeast Minahasa Regency during the covid-19 pandemic. This research is categorized as quantitative research and uses associative research methods. The population in this study are tourists who visit tourism objects in Southeast Minahasa district. The sample used was 96 respondents. The data collection method used confirmatory factor analysis, multiple linear regression analysis, F test, t test, using the SPSS 25 application program. The results showed that Product, Price, Place and Location factors simultaneously had a positive and significant effect on Tourist Visiting Interest.